Asymptotic Behaviour of Blow-up for Solutions of Semilinear Reaction-diffusional Systems (Journal of Partial Differential Equations, 1998)
In this paper, we consider Lhe asymptotic behaviour of the solutions or semilinear reaction-diffusional systems and obtain the growth rate.
Keywords: Blow-up point; reaction-diffusional system; similar variables